Matsucoccus bast scale in Pinus pinaster forests: a comparison of two systems by means of emergy analysis. (1st June 2015) - Turcato, C.; Paoli, C.; Scopesi, C.; Montagnani, C.; Mariotti, M.G.; Vassallo, P.
Abstract: The bast scale ( Matsucoccus feytaudi ) is responsible for the destruction of most of the Pinus pinaster forests in the Mediterranean area, causing resination, defoliation and subsequent death of the trees. This study was carried out in Cinque Terre National Park (Italy), in which pinewood are partially affected by the bast scale M. feytaudi . A whole system evaluation is here proposed aiming at the assessment of the impacts, both on the environmental and economic side, arising from the P. pinaster losses in a certain territory. To this aim we compared a pinewood without visible damages from bast scale with a clearly damaged pinewood by means of emergy analysis. Bast scale reduced the arboreal composition of the stand favouring understorey species sprouting, which benefitted of increasing sunlight level caused by affected tree crowns reduction or trees fall. As a consequence of the changed forest's condition the system suffered an ecosystem services provision loss equal to 2250 Em€ ha −1  year −1 that, if extended to the entire surface of the Cinque Terre National Park lead to a total loss of a million of Euro per year.